O significado do pai para a psique: da interdição estruturante à construção da autonomia - Lima Filho, Alberto Pereira (1999)
The text is divided into two interrelated sections. The first section encompasses a theoretical overview of developmental psychology through the perspective of Analytical Psychology. It focuses on the patriarchal dynamism ranging from the paternal interdiction up to the struggle towards autonomy. The following aspects are taken into account: the matriarchal roots of the psyche and the passage to the archetypal orientation of the father; the Oedipal complex and its modes of resolution; Jung's concept of the father's functions; the archetypes of the hero and the heroine (and related topics) as paradigms for the structuring of the ego; passage rites and their meaning; the Lagos-Eras distinction and interrelation; the Nomos, which is estimated according to a progressive structural development; the overcoming of matriarchal disturbances by functional father interventions; the outcome to be expected from disfunctional father interventions. The second section includes the analyses of eight clinical cases, both men and women, at different ages, intended to reveal a comprehensive picture of the cultural ideology which prevails in the Brazilian society. A disfunctional and one-sided father image underlies concepts which unconsciously determine what is and what is not to be included in the individual' s life, leading to an extended submission to negative paternal dominance as well as to the postponement of the alterity dynamism